Dexamethasone Role in Opioid Sparing Pediatric Below Umbilical Surgery Anesthesia - Randomized Control Trial (Medical Forum Monthly, 2026)
Objective: To examine the differences between dexamethasone ketamine opioid sparing anesthesia technique with propofol ondansetron in pediatric surgery anesthesia.Study Design: Randomized control trial studyPlace and Duration of Study: This study was conducted at the operating rooms and ICU of Mohiuddin teaching hospital, Mirpur, Azad Kashmir from June 2025 to December 2025.Methods: Post approval from institutional ethical review board, we randomized ASA I-II pediatric patients. Fifty subjects stratified into two sections, Dexamethasone Ketamine (DK ) and Propofol ondansetron ( PO). All patients underwent below umbilical surgeries with oro tracheal tube. Primary outcome of interest was prolongement of duration of analgesia and secondary outcomes nausea and vomiting ,rescue opioid analgesia and wound condition.Results: Fifty pediatric patients meeting inclusion criterion split into two sections at random: DK and PO. The duration of block analgesia improved in group DK than group PO but remained insignificant (p = 0.065). Dexamethasone also spared the rescue opioid in group DK as compared to group PO (p = 0.149). Dexamethasone ketamine combo improved the duration and decrease rescue opioid consumption with significant reduction in postoperative pain (p <0..005) and nausea vomiting (p = 0.297). Wound condition remained satisfactory during hospital stay and in follow up at OPD.Conclusion: Dexamethasone ketamine combo provides longer duration of analgesia in pediatric surgical patients alongside decreased opioid consumption and lower incidence of nausea and vomiting compared to propofol ondansetron combo making it a better opioid sparing anesthesia technique in multimodal analgesia with good wound healing in pediatric surgery anaesthesia.